2015
DOI: 10.3390/ijms160922081
|View full text |Cite
|
Sign up to set email alerts
|

Maternal PUFA ω-3 Supplementation Prevents Neonatal Lung Injuries Induced by Hyperoxia in Newborn Rats

Abstract: Bronchopulmonary dysplasia (BPD) is one of the most common complications of prematurity, occurring in 30% of very low birth weight infants. The benefits of dietary intake of polyunsaturated fatty acids ω-3 (PUFA ω-3) during pregnancy or the perinatal period have been reported. The aim of this study was to assess the effects of maternal PUFA ω-3 supplementation on lung injuries in newborn rats exposed to prolonged hyperoxia. Pregnant female Wistar rats (n = 14) were fed a control diet (n = 2), a PUFA ω-6 diet (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…While exposure to 75% oxygen from birth did not decrease body weight at day 14, it did decrease body weight by an additional 11% in growth-restricted pups. Other investigators have shown that exposure to more extreme hyperoxia decreases body weight (18,19). Our data suggest BPD could arise from oxygenmediated lung injury in combination with effects arising from oxygen-mediated growth restriction.…”
Section: Discussionsupporting
confidence: 51%
“…While exposure to 75% oxygen from birth did not decrease body weight at day 14, it did decrease body weight by an additional 11% in growth-restricted pups. Other investigators have shown that exposure to more extreme hyperoxia decreases body weight (18,19). Our data suggest BPD could arise from oxygenmediated lung injury in combination with effects arising from oxygen-mediated growth restriction.…”
Section: Discussionsupporting
confidence: 51%
“…On this regard, several clinical studies showed that the maternal supplementation of vitamin A, which exerts antioxidant activity, during the late phase of pregnancy is effective in decreasing BPD incidence in newborn infants. 3 Moreover, in line with these findings, Sharma et al 4 found in the rat model that the maternal supplementation with polyunsaturated fatty acids u-3 significantly decreases the neonatal onset of BPD, especially protecting the reduction of alveolarization caused by the hyperoxia-induced oxidative damage.…”
mentioning
confidence: 80%
“…50 The impact of maternal lipoproteins in utero is demonstrated by correlations between maternal lipoproteins and cord blood lipoproteins and decreased cord blood total HDL and LDL concentrations in premature infants with respiratory distress syndrome 51 and also by a recent animal study wherein supplementation of the maternal diet with ω-3 polyunsaturated fatty acids during pregnancy decreased neonatal lung injury. 52 Diet affects lipoprotein concentrations in preterm infants. Increased apoprotein A1 and HDL concentrations have been demonstrated in enterally fed preterm infants and preterm infants on TPN with early enteral feedings versus infants receiving TPN alone.…”
Section: Discussionmentioning
confidence: 99%